CRISPR/Cas genome editing improves abiotic and biotic stress tolerance of crops - Li, Yangyang; Wu, Xiuzhe; Zhang, Yan; Zhang, Qiang (Frontiers in Genome Editing, 2022)
Abiotic stress such as cold, drought, saline-alkali stress and biotic stress including disease and insect pest are the main factors that affect plant growth and limit agricultural productivity. In recent years, with the rapid development of molecular biology, genome editing techniques have been widely used in botany and agronomy due to their characteristics of high efficiency, controllable and directional editing. Genome editing techniques have great application potential in breeding resistant varieties. These techniques have achieved remarkable results in resistance breeding of important cereal crops (such as rice, wheat, maize, etc.), fruit, and vegetable crops (such as tomato, cucumber, etc.). Among them, CRISPR/Cas (clustered regularly interspaced short palindromic re-peats/CRISPR-associated) provides a guarantee for the stability of crop yield worldwide. In this paper, the development of CRISRR/Cas and its application in different resistance breeding of im-portant crops are reviewed, the advantages and importance of CRISRR/Cas technology in breeding are emphasized, and the possible problems are pointed out.